2021
DOI: 10.1037/xge0000890
|View full text |Cite
|
Sign up to set email alerts
|

Visual working memory items drift apart due to active, not passive, maintenance.

Abstract: How are humans capable of maintaining detailed representations of visual items in memory? When required to make fine discriminations, we sometimes implicitly differentiate memory representations away from each other to reduce inter-item confusion. However, this separation of representations can inadvertently lead memories to be recalled as biased away from other memory items, a phenomenon termed repulsion bias. Using a non-retinotopically specific working memory paradigm, we found stronger repulsion bias with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 92 publications
(232 reference statements)
4
34
0
Order By: Relevance
“…Importantly, these biases are not simply inherited from perceptual processing: as noise accumulates in memory over time (reducing the signal-tonoise if memory items), and the need to keep memoranda distinct grows, a corresponding increase in the repulsion bias is observed. Importantly, very recent work (performed since the first presentation of the experiments in the current article) has confirmed various key aspects of our framework: As memories get weaker, biases switch from repulsion to attraction (Lively et al, 2021), and repulsion biases increase with longer memory delays (Scotti et al, 2021).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Importantly, these biases are not simply inherited from perceptual processing: as noise accumulates in memory over time (reducing the signal-tonoise if memory items), and the need to keep memoranda distinct grows, a corresponding increase in the repulsion bias is observed. Importantly, very recent work (performed since the first presentation of the experiments in the current article) has confirmed various key aspects of our framework: As memories get weaker, biases switch from repulsion to attraction (Lively et al, 2021), and repulsion biases increase with longer memory delays (Scotti et al, 2021).…”
Section: Discussionsupporting
confidence: 72%
“…Past work has found evidence for attraction biases (Brady et al, 2011; Brady & Alvarez, 2011; 2015; Dubé et al, 2014; Dubé & Sekuler, 2015; Huang & Sekuler, 2010; Lew & Vul, 2015; Lorenc et al, 2018; Utochkin & Brady, 2020), repulsion biases (O’Toole & Wenderoth, 1977; Rauber & Treue, 1998; Scotti et al, 2021; Suzuki & Cavanagh, 1997), or both (Bae & Luck, 2017; Golomb, 2015; Rademaker et al, 2015). Our model and empirical work identifies several key factors that drive these effects and provides evidence that both can arise even in similar paradigms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic errors may substantially increase after 5 s, the longest delay interval we used. Moreover, it has been shown that the mean recall errors for orientation 48 , 49 or color 50 increased over memory delays when multiple items were presented and when the items were actively maintained in memory 50 . More studies are needed to examine where, when, and how systematic and unsystematic errors occur.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others showed that unsystematic error accumulated within the first 800 ms of the delay and stayed stable 6 . Similarly, some suggested that most systematic errors accumulated within the first second of the delay 6 , 8 , whereas others showed an increase in the systematic bias with delays up to 3 s 9 , 48 50 . One of the primary sources of VSWM errors across time may be noise accumulation over memory maintenance.…”
Section: Introductionmentioning
confidence: 99%